Scientific activity and life journey the first rector of the Ukrainian Agricultural Academy P.D. Pshenichniy - POLYVACH, Maria (Journal of Education, Technology and Computer Science, 2013)
The article is devoted to an outstanding scientist in zootechnics P.D. Pshenichny, disclosing his life journey and scientific accomplishments. He was a highly educated scientist, investigative experimenter, is closely associated with the production, farm workers, was an example of true national scholar and active public figure.